A model's competence influences false-belief attribution in preschoolers. Issue 1 (2nd January 2020) - Zmyj, Norbert; Seehagen, Sabine
ABSTRACT: This study investigated whether 4–5-year-olds' attribution of false beliefs is influenced by a person's previously demonstrated competence. The children ( N = 96) were presented with two protagonists who labelled familiar objects either correctly or incorrectly. Subsequently, these protagonists labelled novel objects differently and it was tested whether children trusted the competent protagonist more than the incompetent protagonist. Finally, one of the protagonists experienced a situation in which it was reasonable to attribute a false belief to this protagonist (change-of-location task). Children were more likely to identify a false belief in the incompetent protagonist, compared to the competent protagonist. This suggests that children's false-belief understanding is susceptible to situational influences.